2023
DOI: 10.1186/s12877-023-04114-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding geriatric models of care for older adults living with HIV: a scoping review and qualitative analysis

Abstract: Background Advances in Human Immunodeficiency Virus (HIV) treatment have reduced mortality rates and consequently increased the number of individuals with HIV living into older age. Despite this, people aged 50 years and older have been left behind in recent HIV treatment and prevention campaigns, and a gold-standard model of care for this population has not yet been defined. Developing evidence-based geriatric HIV models of care can support an accessible, equitable, and sustainable HIV health … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…People with HIV experience delays in treatment in general due to fear of disclosure, loneliness, social isolation, and depression brought on by the stigma attached to the virus, and they may also perceive discrimination from healthcare professionals, which makes them reluctant or unwilling to seek medical attention [44]. An ideal care model [45] identified three core care components: collaboration and integration, organization of geriatric care, and support for holistic care that may enhance the adequate provision of geriatric care to individuals living with HIV. A holistic person-centered care approach for older adults with HIV needs to incorporate financial, social, emotional/spiritual, and physiological aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with HIV experience delays in treatment in general due to fear of disclosure, loneliness, social isolation, and depression brought on by the stigma attached to the virus, and they may also perceive discrimination from healthcare professionals, which makes them reluctant or unwilling to seek medical attention [44]. An ideal care model [45] identified three core care components: collaboration and integration, organization of geriatric care, and support for holistic care that may enhance the adequate provision of geriatric care to individuals living with HIV. A holistic person-centered care approach for older adults with HIV needs to incorporate financial, social, emotional/spiritual, and physiological aspects.…”
Section: Discussionmentioning
confidence: 99%
“…These issues could have significantly impacted the living experiences of older PLWHA. There were contributing observations of ageism, sexism [18,33], and HIV-related stigma [17,19,22,23,26,28,29,33,37,[41][42][43][44][45]47].…”
Section: Discussionmentioning
confidence: 99%
“…As older persons with HIV age, specialized care provided by, or in consultation with, geriatric care specialists, including geriatricians and geriatric clinical nurse specialists) are healthcare professionals who specialize in providing comprehensive medical care and chronic illness management for older adults (Brañas et al, 2019), can address geriatric syndromes commonly present in older persons with HIV (Greene et al, 2015). Geriatric care specialists manage geriatric syndromes, provide comprehensive medication management, optimize quality of life, and promote healthy aging (Kokorelias et al, 2023). Through the development of tailored care plans and interdisciplinary collaboration, they can provide specialized expertise to enhance the overall well-being and outcomes of persons aging with HIV (Guaraldi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into impactful and appropriate models of care for older persons living with HIV are limited. We conducted a systematic synthesis of existing models of geriatric HIV care to identify the key components and inform novel geriatric-HIV models of care within Canada (Kokorelias et al, 2023). Our review found that, while numerous models have been implemented with geriatricians taking on responsibilities ranging from consultation to leadership roles, no model considered the role of culturally-appropriate care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation